2017
DOI: 10.1111/evo.13254
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization increases mitochondrial production of reactive oxygen species in sunfish

Abstract: Mitochondrial dysfunction and oxidative stress have been suggested to be possible mechanisms underlying hybrid breakdown, as a result of mito-nuclear incompatibilities in respiratory complexes of the electron transport system. However, it remains unclear whether hybridization increases the production of reactive oxygen species (ROS) by mitochondria. We used high-resolution respirometry and fluorometry on isolated liver mitochondria to examine mitochondrial physiology and ROS emission in naturally occurring hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Our results suggest that hybrid individuals are faced with increased ROS production. This was also observed in isolated mitochondria of sunfish hybrids when these were compared with the parents (Du et al, 2017). Regulation of the AOS can be considered as an indirect cost of oxidative stress (Costantini, 2014).…”
Section: Oxidative Stress As the Cost Of Hybridizationmentioning
confidence: 65%
See 2 more Smart Citations
“…Our results suggest that hybrid individuals are faced with increased ROS production. This was also observed in isolated mitochondria of sunfish hybrids when these were compared with the parents (Du et al, 2017). Regulation of the AOS can be considered as an indirect cost of oxidative stress (Costantini, 2014).…”
Section: Oxidative Stress As the Cost Of Hybridizationmentioning
confidence: 65%
“…Boosted anti-oxidant defences in the damselfly (Lestes viridis) and blackbirds (Turdus merula) lead to a trade-off in immune function (Eikenaar et al, 2018;Janssens and Stoks, 2018), while in hybrids of marine copepod, reduced fecundity was associated with disrupted oxidative balance (Barreto and Burton, 2013). Du et al (2017) suggested that increases in ROS production and oxidative stress contribute to the relatively poor competitive ability of sperm in sunfish F 1 hybrids in comparison with that of parental species.…”
Section: Oxidative Stress As the Cost Of Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…TMLHE is involved in carnitine biosynthesis, an antioxidant that might protect mitochondria from oxidative stress [ 84 ]. The control of oxidative stress is an important component of many aspects of physiology and reproduction, and its disruption has been reported to occur in situations of hybridization [ 74 , 85 , 86 ]. These genes are thus candidates to have been affected by cytonuclear co-evolution during and after the hybridization events.…”
Section: Discussionmentioning
confidence: 99%
“…The maximal activity (V max ) of citrate synthase (CS) and cytochrome c oxidase (COX) is commonly used as a measure of mitochondrial density (Larsen et al, 2012), so would be expected to correlate with measurements of mitochondrial respiration rate per unit mass of tissue. Activity was assayed at 12°C as previously described (Du et al, 2017;Dawson et al, 2018) using a SpectraMaxPlus 384 spectrophotometer (Molecular Devices, Sunnyvale, CA, USA). Samples were homogenized in 20 volumes of ice-cold homogenization buffer [in mmol l −1 : 100 KH 2 PO 4 , 1 EGTA, 1 EDTA and 1 phenylmethylsulfonyl fluoride (PMSF); pH 7.3].…”
Section: Gill Tissue Mitochondrial Enzyme Activitymentioning
confidence: 99%